Nitrogen balance and gap of a high yield tropical soybean crop under irrigation - Zambon, Leandro Moraes; Umburanas, Renan Caldas; Schwerz, Felipe; Sousa, Jackellyne Bruna; Barbosa, Everton Servilho Teixeira; Inoue, Letícia Pacheco; Dourado-Neto, Durval; Reichardt, Klaus (Frontiers in Plant Science, 2023)
Nitrogen (N) is the most extracted and exported element by the soybean crop. In high yield tropical environments with irrigation, little is known about N accumulation in different soybean plant organs as well as the N balance. The objective of this study was to characterize soybean growth, N accumulation in plant organs, N balance, and N gap in a high yield tropical environment. This study was performed in a homogeneous field, in a soil with low organic matter, with 20 kg ha-1 of N, under furrow fertilization. Evaluations were performed ten times, temporelly distributed from emergence to senescence. The soybean cultivar used was ‘RK7518 IPRO’ and was sown with row spacing of 0.45 m and a seeding rate of 300,000 plants ha-1. Plant N partition, N from the biological N fixation (BNF), grain yield, crop harvest index (HI), N harvest index (NHI) with and without root contribution were evaluated. Also, at the grain filling stage the N gap was evaluated from the soil by difference between whole plant accumulated N and the amount of N from BNF. The average grain yield was 6,470 kg ha-1 and leads to a negative partial balance of N of -33.4 and -42.8 kg[N] ha-1 with and without roots, respectively. The N gap from the soil was 231.7 kg[N] ha-1. It is recommended to adopt techniques that increase the efficiency of BNF and the soil N accumulation to balance these production systems in the medium to long term.